If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -1 = x + 27 Reorder the terms: -1 + 13x = x + 27 Reorder the terms: -1 + 13x = 27 + x Solving -1 + 13x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1 + 13x + -1x = 27 + x + -1x Combine like terms: 13x + -1x = 12x -1 + 12x = 27 + x + -1x Combine like terms: x + -1x = 0 -1 + 12x = 27 + 0 -1 + 12x = 27 Add '1' to each side of the equation. -1 + 1 + 12x = 27 + 1 Combine like terms: -1 + 1 = 0 0 + 12x = 27 + 1 12x = 27 + 1 Combine like terms: 27 + 1 = 28 12x = 28 Divide each side by '12'. x = 2.333333333 Simplifying x = 2.333333333
| 5/3x:3/1 | | -9(x+3)+4x+5=6x+12 | | 8(31.25+-0.5y)+4y=250 | | 3(30+s)=4(s+1a) | | 2w+6=30 | | 2m+1=6m+2 | | 8(31.25+-0.5)+4y=250 | | x^4+6x^2+2x=0 | | 21m+36=3m | | 14x-21=49 | | (1/6x-5)-(6/5-6x) | | 8(x-9)=12 | | -3.4=.4j | | 49=25/1y | | 7c-7b=x | | 3(x+7)-4(x+3)=10 | | 12+50=949.88 | | 6y+(-4)= | | -2x=5x-9x+16-10 | | 7=.75*20+4 | | -3/4*8 | | 3+66x=33x+22 | | -x/4=-22 | | 4(7x+1)=312 | | .6h=1.8 | | 2(3y-6)= | | 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 |